Effect of annealing and potassium substitution on the thermoelectric and magnetic properties of directionally grown Bi2Sr2Co2Oy ceramics - Gizem Çetin; Bekir Özçelik; Mehmet Gürsul; Miguel Angel Torres; Maria A. Madre; Andres Sotelo (Boletín de la Sociedad Española de Cerámica y Vidrio, 2020)
Bi2Sr2−xKxCo2Oy (x = 0.0, 0.025, 0.050, 0.075, 0.100, 0.125, and 0.15) ceramic materials have been fabricated using a classical ceramic process, followed by texturing through directional solidification. SEM analysis of samples, before and after annealing has shown that grains were aligned along the growth direction. While as-grown samples have several phases, besides the thermoelectric one, the annealed ones show much higher thermoelectric phase content. In addition, K-substitution increases the thermoelectric phase content and enhances grain orientation. These improvements decrease the electrical resistivity without significant changes in Seebeck coefficient. The maximum power factor value for 0.10K-substituted annealed samples has been found as 0.20 mW/K2 m. This is superior to the highest reported for hot-pressed materials. However, all samples have similar magnetic properties. Resumen: Materiales cerámicos de composición Bi2Sr2−xKxCo2Oy (x = 0.0, 0.025, 0.050, 0.075, 0.100, 0.125, y 0.15) se han preparado por medio del proceso cerámico tradicional, seguido por un texturizado a través de una solidificación direccional. El análisis de las muestras por medio del SEM, antes y después del recocido, ha mostrado que los granos se han alineado en la dirección del crecimiento. Mientras que las muestras crecidas presentan varias fases, además de la termoeléctrica, las recocidas tienen mayor cantidad de fase termoeléctrica. Además, la substitución con potasio aumenta la proporción de fase termoeléctrica y mejora la orientación de los granos. Estas mejoras llevan a una disminución de la resistividad eléctrica sin modificar en gran medida el coeficiente de Seebeck. El mayor valor del factor de potencia se ha obtenido en muestras recocidas con substituciones del 0.10 K, 0.20 mW/K2 m. Este valor es mayor que el mayor reportado en materiales texturizados por prensado uniaxial en caliente. Sin embargo, la diferencia en el contenido de K, no produce variaciones en las propiedades magnéticas.